Homestead Agriculture in Drought and Salinity Affected Areas: Addressing climate resilience, livelihoods and nutrition challenges - Gonsalves, Julian Francis; Or, Thy; Yim, Soksophors; Tong, Chantheang; Vitou, Sam (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
The primer is offering new options or opportunities for households in Cambodia to prepare for future climate change, by diversifying their livelihoods with crops, trees and small livestock in their homesteads.